DESIGN OF MAGAZINE STATION SYSTEM FOR MODULAR MECHATRONICS SYSTEM - Syahril Ardi; Dimas Widyasmoro Hidayat (Technologic, 2011)
Developing to mechatronics module system has been a need for complementary mechatronics learning system that a whole and integration in the conveyor belt system. We had designed a station that can use function of sensors for knowing and determining the position of work part as accurately. The work process of sensory system station is to know and to determine the position of work part on the pallet, is the position where definition or not. After that, this position will be informed to turning device station. Based on the testing design of sensory system station, the use of 3 fiber optic sensor (NPN type with dual adjuster, input 12-24 volt DC), the sensor can read for 4 different position of the work part. The distance optic cable from fiber optic sensor to work part is 8 mm. While, the distance of reading fiber optic sensor is 37 mm (if vertical with the part, but it can be adjusted with the dual adjuster), and the minimum reading of diameter is 0.03 mm.